Implentasi Metode Tahsin Tilawah dalam Meningkatkan Kemampuan Membaca Al-Qur’an di TPQ Umul Qur’an Kemang Kabupaten Bogor - Oktapiani, Putri; Yunizul Pesha, Indry Nirma; Rivani, Falizar (Al-Wasathiyah: Journal of Islamic Studies, 2025)
The Qur'an is an important aspect of Islamic education, becoming the basis for understanding and practicing the teachings in it. This research is motivated by the phenomenon in TPQ Ummul Qur'an, some students still have difficulty reciting hijaiyah letters, understanding long and short letters, and applying the law of tajweed. The focus of the research is the implementation of the tahsin recitation method in learning to read the Qur'an. The purpose of this study is to find out: The implementation of the tahsin recitation method, the improvement of the ability to read the Qur'an, as well as the supporting and inhibiting factors in TPQ Ummul Qur'an. The research uses a qualitative approach of descriptive analysis with data collection techniques through observation, interviews, and documentation. The results of the study show that: (1) the implementation of the tahsin recitation method is applied gradually and systematically through the introduction of makhraj and the nature of letters, tajweed exercises, and evaluation of readings with talaqqi and musyafahah. Of the 20 students, 14 showed precision and good mastery of tajweed, while the other 6 were still inconsistent and stammered. This shows that the application of the tahsin method is effective. (2) the tahsin recitation method is able to improve the ability to read the Qur'an in the ability to read the Qur'an, showing that the tahsin recitation method has a positive impact on improving the ability of students to read the Qur'an. Of the 20 students studied, 14 students showed that they were able to apply tahsin recitation and mastery of tajweed, while 6 students still did not apply tahsin recitation consistently. These findings show that the implementation of the tahsin method has been effective, guidance is needed (3) supporting and inhibiting factors in the implementation of the tahsin recitation method in TPQ is effective and has a positive impact on improving students' ability to read the Qur'an Factors that support success include patience, teacher consistency, parental and institutional support, the main obstacles include lack of concentration and discipline of students, limited learning facilities, as well as a less supportive home environment.